Об эффекте фокусировки когерентного дифракционного излучения полупараболической мишенью - Потылицын А. П. Александр Петрович; Вуколов А. В. Артем Владимирович; Шевелев М. В. Михаил Викторович; Балдин А. А. Антон Александрович; Блеко В. В. Владислав Витольдович; Блеко В. В. Витольд Владиславович; Кобец В. В. Валерий Васильевич; Каратаев П. В. Павел Владимирович; Кочарян В. Р. Ваган Рашидович (2024, 2024)
Заглавие с экрана